Analisis Yuridis Dugaan Pelanggaran Kartel dalam Kuota Impor Garam Industri oleh AIPGI : Studi Kasus (Putusan Nomor 09/KPPU-I/2018) - Adinda Alviana; Anna Nur Hikmah; Findia Putri Marselina; Kharisma Eka Putri; Muhammad Aldi Pratama; Muhammad Alif Baiquni; Nur Syahida; Saira Shabrina; Siti Nurcahyati; Syafiul Muhlasin; Tanya Ketrin Mamonto; Tiara In Gayatri (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to find out how the form and agreement of the distribution of salt import quotas for various food industries carried out by business actors through the Indonesian Salt Producers Importers Association (AIPGI) in the perspective of business competition law in Indonesia. In addition, this study also aims to analyze whether the action meets the elements of violation of Article 11 of Law Number 5 of 1999, as well as its legal and economic impact on market structure, business competition, prices, and supply in the food and beverage industry. This research uses a normative juridical method with a statutory approach and a case study of ICC Decision Number 09/ICC-I/2018, and is supported by secondary data from relevant legal literature and laws and regulations. The results of the study show that the distribution of import quotas by AIPGI is carried out without a valid legal basis and has the potential to lead to cartel practices, which leads to market control by a handful of business actors, price distortions, supply scarcity, and increased production costs in the food and beverage sector. Although ICC stated that it was not legally proven that there had been a violation of Article 11, this collective practice was contrary to the principle of fair competition and created an oligopolistic market structure. These findings underscore the importance of transparency, oversight of business associations, and consistent law enforcement to maintain fair business competition in Indonesia.